Impact of PCB and p,p'-DDE contaminants on human sperm Y : X chromosome ratio: Studies in three European populations and the inuit population in Greenland - T. Tiido; A. Rignell Hydbom; BAG Jonsson; YL Giwercman; HS Pedersen; B. Wojtyniak; JK Ludwicki; V. Lesovoy; V. Zvyezday; M. Spano; MANICARDI, Gian Carlo; D. Bizzaro; et al. (Environmental Health Perspectives, 2006)
Recent studies indicate that persistent organohalogen pollutants (POPs) may contribute to sex ratio changes in offspring of exposed populations. Our aim in the present study was to investigate whether exposure to 2,2',4,4',5,5'-hexachlorobiphenyl (PCB-153) and dichlorodiphenyldichloroethene (pp'-DDE) affects sperm Y:X chromosome distribution. SUBJECTS AND METHODS: We obtained semen and blood for analysis of PCB-153 and pp'-DDE levels from 547 men from Sweden, Greenland, Poland (Warsaw), and Ukraine (Kharkiv), with regionally different levels of POP exposure. The proportion of Y- and X-chromosome-bearing sperm in the semen samples was determined by two-color fluorescence in situ hybridization analysis. RESULTS: Swedish and Greenlandic men had on average significantly higher proportions of Y sperm (in both cohorts, 51.2%) and correspondingly higher lipid-adjusted concentrations of PCB-153 (260 ng/g and 350 ng/g, respectively) compared with men from Warsaw (50.3% and 22 ng/g) and Kharkiv (50.7% and 54 ng/g). In the Swedish cohort, log-transformed PCB- 153 and log-transformed pp'-DDE variables were significantly positively associated with Y-chromosome fractions (p-values 0.04 and < 0.001, respectively). On the contrary, in the Polish cohort PCB-153 correlated negatively with the proportion of Y-bearing fraction of spermatozoa (p = 0.008). CONCLUSIONS: The present study indicates that POP exposure might be involved in changing the proportion of ejaculated Y-bearing spermatozoa in human populations. Intercountry differences, with different exposure situations and doses, may contribute to varying Y:X chromosome ratios.